Evaluasi Pengelolaan Strategi dan Pengelolaan Hubungan Dalam Implementasi Teknologi Informasi Menggunakan COBIT 5 Pada Badan Perencanaan Pembangunan, Penelitian, dan Pengembangan Daerah Kota Batu - Teguh Pribadi; Widhy Hayuhardika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
As the organizer of government activities, Batu City Government has full responsibility in carrying out activities related to government activities in Batu City. Batu City Government needs a vision, mission and program to form a good and orderly Batu City. However, the implementation of information technology in carrying out the existing programs in the Batu City RPJMD requires an evaluation. Evaluation is needed along with the development of the technology used. In integrating the existing vision and mission with information technology, Batu City needs an evaluation to achieve its objectives. This evaluation uses the COBIT version 5 framework and uses the Align, Plan, and Organize (APO) domain that focuses on the APO08 process, namely Manage Relationship and APO02 processes, namely Manage Strategy. Based on observations of data collection on BAPPELITBANGDA Kota Batu, the APO02 Manage Strategy process has a Capability level at level 0 (zero) worth 42.79%. And in the APO08 process, the Relationship Management has a Capability level at level 0 (zero) worth 40.27%. With a gap to the Targeted level each process is 3 levels of the current Capability level. This evaluation also produced several recommendations to help BAPPELITBANGDA Batu City in achieving Capability Levels of the process assessed in this study according to the targeted level desired by this organization.